Edaphic and microclimatic controls over permafrost response to fire in interior Alaska - Dana R Nossov; M Torre Jorgenson; Knut Kielland; Mikhail Z Kanevskiy (Environmental Research Letters, 2013)
Discontinuous permafrost in the North American boreal forest is strongly influenced by the effects of ecological succession on the accumulation of surface organic matter, making permafrost vulnerable to degradation resulting from fire disturbance. To assess factors affecting permafrost degradation after wildfire, we compared vegetation composition and soil properties between recently burned and unburned sites across three soil landscapes (rocky uplands, silty uplands, and sandy lowlands) situated within the Yukon Flats and Yukon-Tanana Uplands in interior Alaska. Mean annual air temperatures at our study sites from 2011 to 2012 were relatively cold (−5.5 ° C) and favorable to permafrost formation. Burning of mature evergreen forests with thick moss covers caused replacement by colonizing species in severely burned areas and recovery of pre-fire understory vegetation in moderately burned areas. Surface organic layer thickness strongly affected thermal regimes and thaw depths. On average, fire caused a five-fold decrease in mean surface organic layer thickness, a doubling of water storage in the active layer, a doubling of thaw depth, an increase in soil temperature at the surface (−0.6 to +2.1 ° C) and at 1 m depth (−1.7 to +0.4 ° C), and a two-fold increase in net soil heat input. Degradation of the upper permafrost occurred at all burned sites, but differences in soil texture and moisture among soil landscapes allowed permafrost to persist beneath the active layer in the silty uplands, whereas a talik of unknown depth developed in the rocky uplands and a thin talik developed in the sandy lowlands. A changing climate and fire regime would undoubtedly influence permafrost in the boreal forest, but the patterns of degradation or stabilization would vary considerably across the discontinuous permafrost zone due to differences in microclimate, successional patterns, and soil characteristics.